A Melanin-Related Phenolic Polymer with Potent Photoprotective and Antioxidant Activities for Dermo-Cosmetic Applications - Davide Liberti; Maria Laura Alfieri; Daria Maria Monti; Lucia Panzella; Alessandra Napolitano (MDPI AG, 2020)
Eumelanins, the dark variant of skin pigments, are endowed with a remarkable antioxidant activity and well-recognized photoprotective properties that have been ascribed to pigment components derived from the biosynthetic precursor 5,6-dihydroxyindole-2-carboxylic acid (DHICA). Herein, we report the protective effect of a polymer obtained starting from the methyl ester of DHICA (MeDHICA-melanin) against Ultraviolet A (UVA)-induced oxidative stress in immortalized human keratinocytes (HaCaT). MeDHICA-melanin was prepared by aerial oxidation of MeDHICA. At concentrations as low as 10 µg/mL, MeDHICA-melanin prevented reactive oxygen species accumulation and partially reduced glutathione oxidation in UVA-irradiated keratinocytes. Western blot experiments revealed that the polymer is able to induce the translocation of nuclear factor erythroid 2-related factor 2 (Nrf-2) to the nucleus with the activation of the transcription of antioxidant enzymes, such as heme-oxygenase 1. Spectrophotometric and HPLC analysis of cell lysate allowed to conclude that a significant fraction (ca. 7%), consisting mainly of the 4,4'-dimer of MeDHICA (ca. 2 μM), was internalized in the cells. Overall these data point to the potential use of MeDHICA-melanin as an antioxidant for the treatment of skin damage, photoaging and skin cancers.